Mitochondrial targets of metformin-Are they physiologically relevant? - Pecinová, Alena; Brázdová, Andrea; Drahota, Zdeněk; Houštěk, Josef; Mráček, Tomáš (BioFactors (Oxford, England), 2019)
Metformin is the most widely prescribed treatment of hyperglycemia and type II diabetes since 1970s. During the last 15 years, its popularity increased due to epidemiological evidence, that metformin administration reduces incidence of cancer. However, despite the ongoing effort of many researchers, the molecular mechanisms underlying antihyperglycemic or antineoplastic action of metformin remain elusive. Most frequently, metformin is associated with modulation of mitochondrial metabolism leading to lowering of blood glucose or activation of antitumorigenic pathways. Here we review the reported effects of metformin on mitochondrial metabolism and their potential relevance as effective molecular targets with beneficial therapeutic outcome.
Keywords: Reactive Oxygen Species; Electron Transport Complex I; Diabetes Mellitus, Type 2; signální transdukce; Gene Expression Regulation; AMP-Activated Protein Kinases; Neoplasms; Hyperglycemia; oxidativní fosforylace; AMPK; diabetes mellitus 2. typu; lidé; Signal Transduction; Hypoglycemic Agents; Humans; hyperglykemie; protein-serin-threoninkinasy; oxidative phosphorylation; Animals; metformin; protinádorové látky; glycerolfosfátdehydrogenasa; Antineoplastic Agents; zvířata; mitochondrie; mitochondria; nádory; Glycerolphosphate Dehydrogenase; reaktivní formy kyslíku; regulace genové exprese; kinasy AMP aktivovaných proteinkinas; proteinkinasy aktivované AMP; AMP-Activated Protein Kinase Kinases; respirační komplex I; Mitochondria; hypoglykemika; Oxidative Phosphorylation; Metformin; Protein Serine-Threonine Kinases